PENGEMBANGAN INOVASI DAN PEMASARAN PRODUK KERUPUK BERBASIS IKAN LELE PADA KARANG TARUNA KARYA 4 DI DESA KEBOCORAN KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS - Sukirno; Eti Wahyuningsih; Herdian Farisi (Jurnal Abdi Masyarakat Multidisiplin, 2022)
Karang Taruna Karya 4 is located in the Leak Village consists of all young people totaling 38 people. Karang Taruna Karya 4 most of which are freshwater fish cultivators (pokdakan) who are still active today. The catfish marketing system used by Karang Taruna Karya 4 is currently very conventional and only relies on buyers from middlemen, restaurants or catfish pecel food stalls. Therefore, new ideas or strategies are needed in terms of Product Development and Innovation, Promotion, as well as product distribution that is right on target, effective and efficient but produces encouraging sales, so that it is expected to advance or improve the economy of all members of Karang Taruna Karya 4. The solution offered to overcome these problems is the development of innovation from catfish to catfish crackers. This community partnership program (PKM) aims to train catfish crackers, marketing management training, training on how to make a Home Industry Food permit (PIRT), and providing capital. This PKM has been implemented for 6 months, from April to September 2021. The community groups in this PKM are 10 members of Karang Taruna Karya 4. The target is after training on making catfish crackers, marketing management training, training on how to make PIRT permits, and providing capital, Karang Taruna Karya 4 can grow by 80%. PKM begins with an interview with the Chairperson of Karang Taruna Karya 4. After that, take care of licensing to related parties, prepare material and non-material needed in the implementation of the PKM, and prepare a coordination team in the PKM. Then the analysis was carried out, namely mentoring training on catfish cracker making, marketing management training, training on how to make PIRT permits. The results of the PKM went smoothly, the openness of the Karang Taruna Karya 4 management in conveying problems and discussions related to solutions to problems were obtained well. Currently, the management of Karang Taruna Karya 4 knows how to collaborate with other parties to market and improve online marketing so that catfish crackers are better known and have more buyers.